Financing Cities : fiscal responsibility and urban infrastructure in brazil, china, India, poland and south africa. - The World Bank (Los Angeles, World Bank, 2007)
This book looks at the practical policy dimension of reconciling two valid policy. perspectives: the need to boost urban infrastructure investment levels and the. need for prudent fiscal management across all levels of government?all in. the context of decentralizing service delivery responsibilities. Several countries. are featured to offer contrasting approaches and experiences. The book addresses. different dimensions for reconciliation between fiscal policy and urban infrastructure. investment: in policy design, analytical understanding, national and international. debt rules, and the poli.
Include Bibliography Reference and Index Material.
Keywords: BUSINESS & ECONOMICS Public Finance; Finance, Public; Finance, Public Case studies